INFLUENCE OF PHILOSOPHY ON ART: TAKE BEETHOVEN'S MUSIC CREATION AS AN EXAMPLE - Yulei, Huo (European journal for philosophy of religion, 2023)
Philosophy is the soul of art, and art is great because of philosophy. All kinds of philosophical thoughts seep into artists' minds like water flooding the beach, affecting their world outlook and outlook on life, and providing theoretical guidance for their artistic creation from aesthetic thoughts to creative methods. Beethoven used musical language to express the deepest worries in the hearts of the advanced people of his time. This paper attempts to explore the internal development law of art philosophy from the perspectives of the orientation of art philosophy, the aesthetic construction of "meaningful form" and "poetic dwelling" of art philosophy, the thinking of the final conclusion of art philosophy, the development destination of art philosophy, and the integration and development. In the long history of art development, the form and function of art are constantly changing. Philosophy provides a continuous source of creative ideas for art and works of art often show profound philosophical views. Kant's lofty aesthetic concept affects the infinite emotional capacity in Beethoven's music. However, the expression of the ubiquitous contradictions and conflicts in Beethoven's music is also deeply influenced by Kant's view of nature. In Beethoven's view, the development of the universe is similar to a person's mental journey, and its essence is also a large symphony or sonata